TEMPERATURE REGIME OF A WELLHEAD COMPRESSOR FOR PUMPING GAS FROM THE ANNULUS OF AN OIL WELL - Kamil R. Urazakov; Bulat M. Latypov; Victor V. Belozerov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2022)
The relevance of the study is caused by the need to reduce the annular gas pressure in oil wells equipped with sucker rod pumping units at high reservoir pressures and the prospective use of wellhead compressors to solve this problem. The operating conditions of the compressors and their operating modes are described. The purpose of the work is to assess the effect of ambient temperature on compressor performance, as well as the advisability of installing a cooling system or thermal insulation. Methods: physical and mathematical model of a single-stage wellhead compressor driven by a pumping unit; the basic equations for describing thermodynamic processes in a compressor are described using the first law of thermodynamics and the law of conservation of gas mass in the compressor cylinder. The developed model takes into account mechanical work, kinetic and thermal energy. At the same time, it is assumed that the pumped gas is ideal. The mathematical model of the compressor operation is implemented in the Python programming language. Results. Analysis of the influence of thermal processes on the wellhead compressor operation showed a significant effect of the ambient temperature on the compressor performance. Based on the results of calculations, it was found that at low temperatures, the compressor performance is higher than at high temperatures. Installing a radiator has a negative impact on compressor performance, especially at low intake pressures. Installation of thermal insulation, on the other hand, made it possible to slightly increase the compressor performance, but not significantly. The main factor affecting the compressor performance is the intake pressure (the value of the pressure drop), therefore, at the compressor start, when the intake pressure approaches the line pressure in the pipeline, the compressor performance is high.